Morphology of new Indian/Indonesian Gamasomorpha and Xestaspis species (Araneae: Oonopidae) - Eichenberger, Beata; Kranz-Baltensperger, Yvonne; Ott, Ricardo; Graber, Werner; Nentwig, Wolfgang; Kropf, Christian (Zootaxa, 2012)
The oonopid genera Gamasomorpha and Xestaspis are very diverse and differ only by the shape of the booklung covers.New Indian/Indonesian Gamasomorpha and Xestaspis species, characterized by sternal furrows consisting of large, drop-like pits are described. Fourteen species are newly described (G. asterobothros n. sp., G. keri n. sp., G. petoteca n. sp., G.insomnia n. sp., G. ophiria n. sp., G. squalens n. sp., G. coniacris n. sp., G. raya n. sp., G. fricki n. sp., G. schmilingi n. sp.,X. kandy n. sp., X. paulina n. sp., X. semengoh n. sp., X. biflocci n. sp.); two species are redescribed (G. seximpressa andG. taprobanica). The high significance of somatic features for species identification, the degree of intraspecific variationand the complexity of the female genitalia are remarkable. The current work suggests that a phylogenetic revision of thegenera Gamasomorpha and Xestaspis and an examination of the validity of the shape of the booklung covers of these two genera are needed.